Hoaks dan Etika Berkomunikasi: Perspektif Al-Qur’an dan Hadis - Taufik R Talalu; Erwin Hafid; Abdul Rahman Sakka (Program Studi Ilmu Al-Quran dan Tafsir, 2022)
Hoaxes are a catalyst for upheaval and violence in people’s lives. The spread of hoaxes is linked to the significance of raising public knowledge about communication ethics. This article clarifies two points. First, the ethics of communicating from the perspective of the Qur’an. Second, communication ethics in the context of hadith. Hoaxes contradict the Qur’anic norms, namely, qaulan sadidan (truth), not lying. This ethic is referenced in the Qur’an al-Nisa’/4: 9 and the Qur’an al-Ahzab/33: 70. The hadith also emphasizes telling the truth. According to Sahih Muslim No. 4721, honesty is the foundation of kindness.